1993
DOI: 10.1001/jama.1993.03500030072035
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Regulation Restricting Medical House Staff Working Hours on the Quality of Patient Care

Abstract: These results suggest that restricted house staff working hours were associated with delayed test ordering by house staff and increased in-hospital complications. While these potentially deleterious effects on the quality of care did not result in statistically significant differences in more serious outcomes, further study at other hospitals is warranted to determine staffing strategies that optimize quality of care for patients, as well as medical education and quality of life for house officers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
3
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(122 citation statements)
references
References 13 publications
4
114
3
1
Order By: Relevance
“…On the other hand, duty hour reform has resulted in fewer residents on duty at any one time, the work intensity of residents may have increased, and continuity of care might have worsened, leading to higher rates of complications, FTR, and mortality in high risk patients. [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, duty hour reform has resulted in fewer residents on duty at any one time, the work intensity of residents may have increased, and continuity of care might have worsened, leading to higher rates of complications, FTR, and mortality in high risk patients. [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no study has proven that fatigue on the part of health care personnel has actually caused errors that harm patients [40]. In contrast, some argue that limiting work hours could actually worsen quality of care [44]. A study of an internal medicine service in New York showed an increase in complications and delays in diagnostic tests after the implementation of shorter work hours [40].…”
Section: Discussionmentioning
confidence: 99%
“…Laine et al (1993) sowie Bollschweiler (1999) untersuchen jeweils den Einfluss der Arbeitszeit auf die Patientenversorgung und stellen dabei fest, dass eine Beschränkung oder Verkürzung der (täglichen) Arbeitszeit die Patientenversorgung verschlechtert. Lockley et al (2004) sowie Landrigan et al (2004) weisen dagegen in ihren Studien nach, dass eine höhere (tägliche und wöchentliche) Arbeitszeit die Qualität der Patientenversorgung durch gestiegene Fehlerhäufigkeit verschlechtert.…”
Section: Stand Der Empirischen Forschungunclassified